Liminal geopolitics: the subjectivity and spatiality of diplomacy at the margins. Issue 1 (6th November 2016) - McConnell, Fiona
Abstract : This paper argues that the lens of liminality has the potential to enrich scholarship in critical geopolitics by offering a nuanced approach to the geographies and ambivalence of political subjectivity. In the context of a perceived proliferation of 'new' actors the paper turns critical attention to what happens at the threshold between the categories of state and non‐state, official and unofficial diplomacy. It asks what such a perspective on diplomacy might mean for understandings of who is, and who should be, a legitimate actor in international politics by turning to the notion of liminality as developed in cultural anthropology. This is a concept that surprisingly has been overlooked in political geography and this paper asks how geographers might engage more productively with it, particularly in light of emergent critical international relations research on liminality as a paradigm for understanding stability and change in institutionalised orders. Empirically, the paper focuses on the articulation of liminal political subjectivities and spatialities through the lens of the Unrepresented Nations and Peoples Organization (UNPO), a coalition of almost 50 stateless nations, indigenous communities and national minorities that currently are denied a place at international diplomatic forums. Drawing on this case study, the paper examines three areas of geopolitical enquiry that the notion of liminality opens up. First is the spatiality of diplomacy in terms of the out‐of‐placeness of liminal actors and the construction of transformative spaces of quasi‐official diplomacy. Second are particular qualities of political subjectivity, including the blurring of boundaries between diplomacy and activism, and the notion of geopolitical shapeshifters. Finally, attention turns to the notion of communitas to draw out the politics of belonging, recognition and legitimacy. The paper concludes by suggesting that the idea of ambivalence that underpins liminality is a useful provocation to take creativity and aspiration seriously in geopolitics.